The Comorbidities Coma Scale (CoCoS): Assessment of Psychometric Properties - N. A. Suponeva; O. A. Kirichenko; K. A. Yatsko; A. A. Zimin; L. A. Legostayeva; D. V. Sergeev; D. G. Yusupova; Yu. V. Ryabinkina; M. A. Piradov; F. Pistoia (Неотложная медицинская помощь, 2023)
INTRODUCTION An increase in the survival rate of patients with severe brain injuries of various origins determines the relevance of the search for approaches to assessing the prognosis of changes in the state of patients with chronic disorders of consciousness (CDC). Concomitant diseases are predictors of the recovery of consciousness and functional independence of patients with CDC. To assess the impact of the level of comorbidity on the prognosis of the patient state, the Comorbidities Coma Scale (CoCoS) is used abroad. However, the lack of a Russian-language version of this scale limits the practical and scientific areas of work with this category of patients.THE AIM of the study was to evaluate the psychometric properties of the developed Russian version of the Comorbidities Coma Scale (CoCoS).MATERIALS AND METHODS As part of the validation study, an assessment of psychometric properties (reliability, validity, sensitivity) was performed on a group of 52 adult patients with traumatic (18/52) and non-traumatic (34/52) brain damage.RESULTS High levels of validity and reliability were obtained (the Spearman’s Rank Correlation Coefficient r=0.98 (p<0.0001), Cronbach’s alpha α=0.73 (p<0.001), Cohen’s kappa κ=0.72 (p<0.0001)). However, when evaluating the CoCoS sensitivity, there were no statistically significant changes in the parameters (p=0.316).CONCLUSION In the present study, a sufficient level of psychometric properties of the Russian-language version of the CoCoS was obtained, which opens up the possibility of a quantitative assessment of comorbidities in unresponsive patients both in scientific research and clinical practice. The scale is available for download on the website of the Group for Validation of International Scales and Questionnaires of the Research Center of Neurology.